DEVELOPMENT OF FUNCTIONAL MATHEMATICAL LITERACY OF STUDENTS HAVING MODERATE SPECIAL EDUCATIONAL NEEDS: APPROACH OF PEDAGOGUES FROM VOCATIONAL REHABILITATION CENTRES - Baranauskienė, Ingrida; Tomėnienė, Laima (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the approach of pedagogues from vocational rehabilitation centres towards the importance of the development of functional mathematical literacy for vocational training of students having moderate special educational needs. It has been attempted to reveal the expression of the abilities of functional mathematical literacy of young people having moderate special educational needs, its importance for vocational training, to discuss the possibilities of the improvement of the education process of mathematics in a heterogeneous classroom, where students with moderate special educational needs learn. 124 pedagogues from Lithuanian vocational training centres and vocational schools who teach young people having moderate and severe special educational needs have participated in the research.